Taking It to the Next Level: A Field Experiment to Improve Instructor-Student Relationships in College. (March 2019) - Robinson, Carly D.; Scott, Whitney; Gottfried, Michael A.
Competing in today's workforce increasingly requires earning a college degree, yet almost half of all enrolled undergraduates do not graduate. As the costs of dropping out of college continue to rise, instructor-student relationships may be a critical yet underexplored avenue for improving college student outcomes. The present study attempts to replicate and extend a prior study that improved teacher-student relationships at the high school level in a college setting. In this registered report, we test whether an intervention that highlights instructor-student commonalities improves similarity, instructor-student relationships, academic achievement, and persistence for undergraduate students in a large, diverse public university. We found that the intervention increased perceptions of similarity but not downstream relational or academic outcomes. Our exploratory analyses provide one of the first investigations suggesting that instructor-student relationships predict an array of consequential student outcomes in college. These findings show a notable relationship gap: instructors perceived less positive relationships with certain student groups, but on average, students perceived equally positive relationships with their instructors.